The utilization of crowdsourcing in video game development in the Finnish video game industry - Paasonen, Ville (2020)
Crowdsourcing is a tool which enables businesses and organizations to tap into the power and knowledge of the crowd by outsourcing tasks normally taken on by in-house resources. By utilizing the crowd, it is possible to initiate software development projects with lesser needs for in-house resources and to utilize creative, quick, and effective task solving capabilities. The creation of value is one of the most important aspects for any business. Value co-creation remains an increasingly emergent and important trend in various markets. Despite the positive results and major possibilities to create value for organizations, businesses and their customers, crowdsourcing seems to have been underutilized in the context of the Finnish gaming industry, due to the lack of available in-formation online. The concept of value remains complex, intangible, and often subjective, but extremely important for any business to understand, and the value creating properties of crowdsourcing remain relatively sparsely studied. This study aims to find out how crowdsourcing activities can create additional value in game development projects of Finnish game studios and organizations. The aim of this study is to spread information of the phenomenon of crowdsourcing and to help businesses realize, how and when crowdsourcing could be utilized in a game development project, by creating a conceptual framework depicting the crowdsourcing process, critical success factors, value creation and perception of value for game studios, organizations, related third party operators and customers.